Prepectoral versus Subpectoral Tissue Expander Breast Reconstruction: A Historically Controlled, Propensity Score–Matched Comparison of Perioperative Outcomes. Issue 1 (July 2021) - Haddock, Nicholas T.; Kadakia, Yash; Liu, Yulun; Teotia, Sumeet S.
Abstract : Background: The rising popularity of prepectoral tissue expander placement with acellular dermal matrices in immediate breast reconstruction has prompted many studies on the safety of this technique. However, a comprehensive propensity-matched, historically controlled trial comparing perioperative outcomes following prepectoral versus partial subpectoral (dual-plane) placement of tissue expanders is lacking. Methods: Retrospective propensity-matched cohort analysis was performed on all patients of two senior reconstructive surgeons who underwent bilateral tissue expander placement following a mastectomy with one of three breast surgeons at a single academic institution from 2012 onward ( n = 260). Two matched groups (prepectoral and partial subpectoral) each consisted of 102 patients. Univariate and multivariable analyses were also performed to contextualize the risks associated with prepectoral reconstruction relative to demographic characteristics and other clinical factors. Results: Compared to dual-plane subpectoral placement, prepectoral placement resulted in similar rates of overall perioperative complications (32 percent versus 31 percent; p = 1.00) and perioperative complications that required operative treatment (21 percent versus 21 percent; p = 1.00). There were no significant differences between the groups in complication rates for hematomas, seromas, impaired wound healing, and infection. Although prepectoral placement was associated with prolonged time to drain removal, those patients completed the expansion process twice as fast, were expanded further in the operating room, and were more than twice as likely to forgo clinic-based expansion. Prepectoral reconstruction was not associated with increased risk for any complications in univariate or multivariable analysis. Conclusions: Prepectoral tissue expander placement permitted greater intraoperative filling of expanders and a reduced likelihood of clinic-based expansion, with no increase in adverse outcomes compared to partial subpectoral placement. Adoption of this technique may reduce unnecessary clinic visits; shorten the delay before adjuvant therapy; and minimize patient apprehension, pain, and discomfort related to clinic-based expansion. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.